Evaluating and modeling variation in site-level maximum carrying capacity of mixed-species forest stands in the Acadian Region of northeastern North America - Aaron R. Weiskittel; Christian Kuehne (The Forestry Chronicle)
Currently no universal approach exists to estimate regional site-level maximum carrying capacity in terms of stand densityindex (SDIMAX) of mixed species stands across contrasting forest ecosystems. Regional research efforts that account forinfluential stand-level variables and species traits are needed to reliably derive SDIMAX under varying environmental conditions and stand characteristics. This study used regionally comprehensive forest inventory data from various permanentsampling efforts to evaluate the effects of contrasting biotic and abiotic stand- and site-level factors on SDIMAX of multiple-species, structurally heterogeneous stands of the climatically diverse Acadian Forest Region of North America. Specifically,we aimed to i) quantify the stand-level maximum size-density line for an array of forest stands found across the study area,irrespective of stand structure; ii) evaluate the relationship between this stand-specific estimate of SDIMAX and various other stand-level attributes; and, iii) develop a generalized SDIMAX prediction model using SDIMAX estimates from objective i) aswell as potential regional drivers of SDIMAX from objective ii). The most influential stand-level factors on SDIMAX were proportion of total stand basal area in hardwood species, basal area weighted mean specific gravity, range in stem diameter, andspecies diversity. Direct climatic variables were not included in our SDIMAX prediction model due to the limited variationexplained, but relationships with elevation and a site quality index based on these climatic variables were. Overall, we con-clude that i) variation in SDIMAX appears to be mostly driven by the softwood to hardwood ratio of the mixed species,structurally complex stands evaluated in our study and ii) the general approach offers a viable framework for estimating sitemaximum carrying capacity at a regional-scale and effectively managing stand density accordingly.